Epidemiology of Cancers in Kashmir, India: An Analysis of Hospital Data. (5th July 2016) - Qurieshi, Mariya A.; Khan, S. M. Salim; Masoodi, Muneer A.; Qurieshi, Uruj; Ain, Quratul; Jan, Yasmeen; Haq, Inaamul; Ahmad, Sheikh Zahoor
Abstract : Cancer is a leading cause of mortality and morbidity in the world. The aim of the present study was to measure the pattern of different cancers in Kashmir, India, a cancer belt with peculiar cancer profile. A hospital based cancer registry was started by the Department of Community Medicine, Government Medical College, Srinagar, in January 2006, wherein information was collected from cancer patients who were diagnosed and treated in the hospital. Data has been analysed for a period extending from January 2006 to December 2012. Descriptive analysis has been done by using statistical software. A total of 1598 cancer patients were admitted during this period. Overall male to female ratio was 1.33 : 1. Stomach cancer was the most commonly reported cancer (25.2%), followed by colorectal cancer (16.4%) and lung cancer (13.2%) among males. For females, colorectal cancer (16.8%), breast cancer (16.1%), and stomach cancer (10.4%) were the most frequently reported cancers in order of frequency. Tobacco related cancers contributed to more than three-fourths of cancers among men and more than half of cancers for women. There is an urgent need to set up a population based cancer registration system to understand the profile of cancers specific to this geographic region.